The taxation of labour vs. capital income A focus on high earners - Hourani, Diana (OECD Publishing, 2023)
This working paper presents novel analysis comparing in a consistent way the tax treatment of labour and capital income across OECD countries, through stylised effective tax rates (ETRs). It shows that dividend income and capital gains are generally subject to lower ETRs than wage income at the personal level. In many countries, capital income is also tax-favoured even when considering taxes paid by both firms and individuals, although the gap between labour and capital income taxation tends to be smaller than when considering only personal-level taxes. The gap between ETRs on labour and capital income varies between countries and grows with income levels in some. The paper highlights that differential tax treatment of labour and capital income can affect the efficiency and equity of tax systems
Keywords: Employment; Taxation